A deep ensemble learning method for single finger-vein identification - Liu, Chongwen; Qin, Huafeng; Song, Qun; Yan, Huyong; Luo, Fen (Frontiers in Neurorobotics, 2023)
Finger-vein biometrics has been extensively investigated for personal verification. Single sample per person(SSPP) finger-vein recognition is one of the open issues in finger-vein recognition. Despite recent advances in deep neural networks for finger-vein recognition, current approaches depend on a large number of training data. Still, they lack the robustness of extracting robust and discriminative finger-vein features from a single training image sample. A deep ensemble learning method is proposed to solve the SSPP finger-vein recognition in this paper. In the proposed method, multiple feature maps were generated from an input finger-vein image, based on various independent deep learning-based classifiers. And, a shared learning scheme is investigated among classifiers to improve their feature representation captivity. The learning speed of weak classifiers is also adjusted to achieve the simultaneously best performance. A deep learning model is proposed by an ensemble of all these adjusted classifiers. The proposed method is tested with two public finger vein databases. The result shows that the proposed approach has a distinct advantage over all the other tested popular solutions for the SSPP problem.